Experimental investigation of the brittle-viscous transition in mafic rocks – Interplay between fracturing, reaction, and viscous deformation. (December 2017) - Marti, Sina; Stünitz, Holger; Heilbronner, Renée; Plümper, Oliver; Drury, Martyn
Abstract: Rock deformation experiments are performed on fault gouge fabricated from 'Maryland Diabase' rock powder to investigate the transition from dominant brittle to dominant viscous behaviour. At the imposed strain rates of γ ˙ = 3 · 10 − 5 − 3 · 10 − 6 s −1, the transition is observed in the temperature range of (600 °C < T < 800 °C) at confining pressures of (0.5 GPa ≤ Pc ≤ 1.5 GPa). The transition thereby takes place by a switch from brittle fracturing and cataclastic flow to viscous dissolution-precipitation creep and grain boundary sliding. Mineral reactions and resulting grain size refinement by nucleation are observed to be critical processes for the switch to viscous deformation, i.e., grain size sensitive creep. In the transitional regime, the mechanical response of the sample is a mixed-mode between brittle and viscous rheology and microstructures associated with both brittle and viscous deformation are observed. As grain size reduction by reaction and nucleation is a time dependent process, the brittle-viscous transition is not only a function of T but to a large extent also of microstructural evolution. Highlights: Transition from brittle cataclastic flow to viscous dissolution-precipitation creep. The brittle-viscous transition shows mixed-mode rheology. Grain size sensitive creep enabled by mineral reactions and nucleation. Microstructural evolution can control the brittle-viscous transition.